DUMITRU LOŞONŢI:TOPONIME ROMÂNEŞTI CARE DESCRIU FORME DE RELIEF (PANGEEA, 2025)
The volume addresses a common theme linguistics and geography, treating etymology toponyms in Romania which describes landforms, appeared to Edit. Clusium, Cluj-Napoca, 2000, 256 pages.